2008
DOI: 10.1007/s10591-008-9075-1
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Perspective on Differentiation of Self, Interpersonal and Psychological Well-Being in Young Adulthood

Abstract: The over-time relationship between differentiation of self and interpersonal and psychological well-being was examined in a sample of young adults in order to test the hypothesis that greater differentiation of self-that is, lower emotional reactivity, better capacity to take an ''I'' position in relationships, less emotional cutoff, and lower fusion with others-predicted greater interpersonal and psychological health. Results of hierarchical regression analyses confirmed that greater Time 1 differentiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
127
1
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(155 citation statements)
references
References 42 publications
13
127
1
14
Order By: Relevance
“…Of the various constructs that compose Bowen Theory, differentiation of self is the most critical to mature development and psychological health. Higher levels of differentiation of self have been linked with better psychological adjustment in adulthood (e.g., Bray, Harvey & Williamson, 1987;Greene, Hamilton & Rolling, 1986;Jenkins, Buboltz, Schwartz & Johnson, 2005), greater capacity for emotional self-regulation, self regulation of attention and behavior, adult attachment security (e.g., Skowron & Dendy, 2004;Skowron, Holmes & Sabatelli, 2003;Thorberg & Lyvers, 2006;Wei, Vogel, Ku & Zakalik, 2005), and fewer psychological symptoms and relationship difficulties (e.g., Bartle-Haring, 1997;Bartle-Haring & Gregory 2003;Peleg, 2002;Schwartz, Thigpen & Montgomery, 2006;Skowron, 2000;Skowron & Friedlander, 1998;Skowron, Stanley & Shapiro, 2009). Studies have also shown that higher levels of differentiation of self are linked to greater marital satisfaction among heterosexual and same-sex couples (e.g., Kosek, 1998;Montes-Berges, 2009;Parsons, Nalbone, Killmer &Wetchler, 2007;Peleg, 2008;Skowron, 2000;Spencer & Brown, 2007), and adults who report greater differentiation of self are at lower risk for engaging in child abuse and other forms of family violence (Skowron, Kozlowski, & Pincus, 2010;Skowron & Platt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Of the various constructs that compose Bowen Theory, differentiation of self is the most critical to mature development and psychological health. Higher levels of differentiation of self have been linked with better psychological adjustment in adulthood (e.g., Bray, Harvey & Williamson, 1987;Greene, Hamilton & Rolling, 1986;Jenkins, Buboltz, Schwartz & Johnson, 2005), greater capacity for emotional self-regulation, self regulation of attention and behavior, adult attachment security (e.g., Skowron & Dendy, 2004;Skowron, Holmes & Sabatelli, 2003;Thorberg & Lyvers, 2006;Wei, Vogel, Ku & Zakalik, 2005), and fewer psychological symptoms and relationship difficulties (e.g., Bartle-Haring, 1997;Bartle-Haring & Gregory 2003;Peleg, 2002;Schwartz, Thigpen & Montgomery, 2006;Skowron, 2000;Skowron & Friedlander, 1998;Skowron, Stanley & Shapiro, 2009). Studies have also shown that higher levels of differentiation of self are linked to greater marital satisfaction among heterosexual and same-sex couples (e.g., Kosek, 1998;Montes-Berges, 2009;Parsons, Nalbone, Killmer &Wetchler, 2007;Peleg, 2008;Skowron, 2000;Spencer & Brown, 2007), and adults who report greater differentiation of self are at lower risk for engaging in child abuse and other forms of family violence (Skowron, Kozlowski, & Pincus, 2010;Skowron & Platt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tai patvirtina moksliniai tyrimai, kurie rodo, kad santykiai šeimoje ir tėvų savidiferenciacijos lygis reikšmingai veikia vaikų, paauglių ir suaugusiųjų psichikos sveikatą. Tėvų savidiferenciacijos lygis siejasi su paauglių patiriamu socialiniu nerimu (Peleg, 2005) (Skowron et al, 2009). Kadangi pasiektas identitetas paauglystėje taip pat siejamas su psichologine gerove, sveikata, sėkminga žmogaus raida ir, atsižvelgiant į santykių šeimoje įtaką paauglio raidai, galima kelti prielaidą, kad savidiferenciacija taip pat galėtų sietis su identiteto krizės sprendimu ar būti tarpiniu veiksniu, nulemiančiu socialinių sąveikų poveikį identiteto formavimuisi.…”
Section: Issn 1392-639x E-issn 2351-6585unclassified
“…Pasak M. Boweno (1978), žmonėms, turintiems žemą savidiferenciacijos lygį, yra sunku atskirti savo mintis ir emocijas nuo kitų asmenų, todėl jie yra linkę patirti daugiau nerimo bei dažnai pasižymi prastesniais psichikos sveikatos rodikliais (Jenkins et al, 2005;Skowron, Dendy, 2004;Skowron et al, 2009). Dėl prastesnio gebėjimo atskirti savo mintis ir jausmus nuo kitų tiek paaugliui, tiek jo tėvams yra sunkiau rasti konstruktyvių būdų, kaip spręsti kylančius konfliktus ir efektyviai bendrauti tarpusavyje.…”
Section: Rezultatų Aptarimasunclassified
See 1 more Smart Citation
“…Higher self-differentiation is associated with higher well-being (Skowron, Stanley, & Shapiro, 2009), and with lower psychological stress (Tuason & Friedlander, 2000), social anxiety, and physiological symptoms (Pelg-Popko, 2002). However, to the best of our knowledge, no previous study has examined the relationship between self-differentiation and psychological well-being and distress in mothers of young children.…”
Section: Introductionmentioning
confidence: 99%